Envelhecimento e rejuvenescimento de software: 20 anos (19952014) - panorama e desafios - Valentim, Nathália Assis (2016)
Although software aging and rejuvenation is a young research held, in its first 20 years a lot of knowledge has been produced. Nowadays, important scientific journals and conferences include SAR-related topics in their scope of interest. This fast growing and wide range of dissemination venues pose a challenge to researchers to keep tracking of the new findings and trends in this area. In this work, we collected and analyzed SAR research data to detect trends, patterns, and thematic gaps, in order to provide a comprehensive view of this research held over its hrst 20 years. Adopted the systematic mapping approach to answer research questions such as: How the main topics investigated in SAR have evolved over time? Which are the most investigated aging effects? Which rejuvenation techniques and strategies are more frequently used?